ADOBE Flash Lite â?? Based Online Laboratory for Mobile Phones - Maiti, Ananda; Maiti, Anindya (International Journal of Interactive Mobile Technologies (iJIM), 2010)
Recently, development of "Microelectronics and VLSI Engineering" Laboratory at IIT Kharagpur (http://lod.iitkgp.ernet.in/netlab), an innovative remote microelectronics device characterization and parameter extraction laboratory has been reported. The laboratory enables students to measure different semiconductor device characteristics and extract device parameters at any time and from anywhere using a Java-enabled web browser. Having pioneered the PC-based online laboratory to enhance microelectronics education, feasibility of use of mobile devices for hardware-based remote experimentation is explored. The work introduced in this paper is a prototype of the use of mobile devices in laboratory education.